Myocardial Electrical Remodeling and the Arrhythmogenic Substrate in Hemorrhagic Shock-Induced Heart: Anti-Arrhythmogenic Effect of Liposome-Encapsulated Hemoglobin (HbV) on the Myocardium. Issue 3 (September 2019) - Takase, Bonpei; Higashimura, Yuko; Hashimoto, Kenichi; Asahina, Haruka; Ishihara, Masayuki; Sakai, Hiromi
ABSTRACT: Introduction: Prolonged low blood pressure <40 mmHg in hemorrhagic shock (HS) causes irreversible heart dysfunction, 'Shock Heart Syndrome' (SHS), which is associated with lethal arrhythmias (ventricular tachycardia or ventricular fibrillation [VT/VF]) leading to a poor prognosis. Methods: To investigate whether the liposome-encapsulated human hemoglobin oxygen carrier (HbV) is comparable in effectiveness to autologous washed red blood cells (wRBCs) for improving arrhythmogenic properties in SHS, optical mapping analysis (OMP), electrophysiological study (EPS), and pathological examinations were performed in Sprague-Dawley rat hearts obtained from rats subjected to acute HS by withdrawing 30% of total blood volume. After acute HS, the rats were immediately resuscitated by transfusing exactly the same amount of saline (SAL), 5% albumin (5% ALB), HbV, or wRBCs. After excising the heart, OMP and EPS were performed in Langendorff-perfused hearts. Results: OMP showed a tendency for abnormal conduction and significantly impaired action potential duration dispersion (APDd) in both ventricles with SAL and 5% ALB. In contrast, myocardial conduction and APDd were substantially preserved with HbV and wRBCs. Sustained VT/VF was easily provoked by a burst pacing stimulus to the left ventricle with SAL and 5% ALB. No VT/VF was induced with HbV and wRBCs. Pathology showed myocardial structural damage characterized by worse myocardial cell damage and Connexin43 with SAL and 5% ALB, whereas it was attenuated with HbV and wRBCs. Conclusions: Ventricular structural remodeling after HS causes VT/VF in the presence of APDd. Transfusion of HbV prevents VT/VF, similarly to transfusion of wRBCs, by preventing electrical remodeling and preserving myocardial structures in HS-induced SHS.